Inter-sector actions to prevent accidents in children education: Teacher's assessments and students' knowledge - Nascimento, Edinalva Neves [UNESP]; Gimeniz-Paschoal, Sandra Regina [UNESP]; Sebastião, Luciana Tavares [UNESP]; Ferreira, Natália de Paula [UNESP] (Faculdade de Filosofia e Ciências, 2013)
Introduction: public health politics and education privilege school for disease prevention and health promotion activities. Objective: this paper describes inter-sector action for childhood accidents prevention, teachers' assessments and the knowledge of the students involved. Methods: it was done in a kindergarten City School in São Paulo interior. Thirty students from the Pre school second year, in the 5-6 age range and the teacher through a signed Consensus Term. The actions were performed in the classroom. Questionnaires were used with the teacher and school books with the children, formulated by speech and language pathology interns, who lead the actions in school. Results: the results showed an improvement in knowledge about children accident risks and forms of prevention by children and teacher. Conclusions: the educational activity was positively evaluated for both participant segments, being suggestive for other classes and/or schools, with health and education professionals' partnership.
Keywords: Accident prevention; Childhood education; Health promotion; Speech and Language pathology